(untitled) (Economic and Political Thought, 2024)
This paper describes the rationale for using a non‑zero neutral countercyclical capital buffer (hereafter nCCyB) to strengthen the banking sector’s stability. The study aims to assess how the nCCyB, as a macroprudential oversight tool, contributes to enhancing the resilience of banking systems and reducing the impact of external economic shocks. The research method used is a critical review of the literature on the subject and an analysis of the source documents of European jurisdictions where a non‑zero neutral countercyclical capital buffer is applied. The literature review points to the significant role of this buffer in reducing imbalances in the banking system and improving resilience to crises. As the study shows, the nCCyB is a valuable component of a macroprudential framework that supports the countercyclical functioning of the banking sector. The conclusions formulated have important implications for policymakers, highlighting the need for a flexible approach to using a non‑zero neutral countercyclical buffer.